1988
DOI: 10.1152/ajprenal.1988.254.5.f634
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the renal response to natriuretic peptide in sheep

Abstract: The ontogeny of the renal response to continuous systemic infusion of atrial natriuretic peptide (ANP) was studied in chronically instrumented fetal, newborn, and adult nonpregnant sheep. Plasma immunoreactive ANP (ANPir) concentrations during low (0.025 microgram.kg-1.min-1) and high rate (0.1 microgram.kg-1.min-1) ANP infusion were similar between each group of animals. Decrease in renal blood flow velocity (RBFV) and rise in renal vascular resistance (RVR) were observed in fetal and newborn lambs during ANP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 0 publications
3
29
1
Order By: Relevance
“…The above-mentioned results may support the suggestion by Granger (1998) that the lack of changes in the glomerular filtration rate results from ANP "redirecting" blood into the medullary part of the kidneys. Conversely, Janssen et al (1994) in adult humans, Robillard et al (1988) in adult sheep, Seino et al (1988) in adult rabbits, andChevalier et al (1988) in adult rats, observed an increased glomerular filtration rate after administration of exogenous ANP. According to Dunn et al (1986) and Marin-Grez et al (1986), enhanced GFR may be a result of haemodynamics changes in the blood vessels of the glomeruli which lead to elevated glomerular filtration pressure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The above-mentioned results may support the suggestion by Granger (1998) that the lack of changes in the glomerular filtration rate results from ANP "redirecting" blood into the medullary part of the kidneys. Conversely, Janssen et al (1994) in adult humans, Robillard et al (1988) in adult sheep, Seino et al (1988) in adult rabbits, andChevalier et al (1988) in adult rats, observed an increased glomerular filtration rate after administration of exogenous ANP. According to Dunn et al (1986) and Marin-Grez et al (1986), enhanced GFR may be a result of haemodynamics changes in the blood vessels of the glomeruli which lead to elevated glomerular filtration pressure.…”
Section: Discussionmentioning
confidence: 96%
“…So far, it has not been clearly established whether and how atrial natriuretic peptide affects renal plasma filtration (Abu-Amarah and Balment 1999;Bidiville et al 1988;Chevalier et al 1988;Garcia-Estan and Roman 1990;Janssen et al 1994;Robillard et al 1988;Seino et al 1988;Semmekrot et al 1990). In our experiment, a lack of relationship was demonstrated between changes in ANP concentration in blood and glomerular filtration rate (coefficient of correlation non-significant at p ≤ 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief increase in renal blood flow occurred in the nonanemic fetuses as well. Consistent with these findings, Robillard et al (8) observed a decrease in renal blood flow and increasin g renal vascular resistance in ovine fetuses receiving exogenous ANP . Furthermore, our findings are consistent with previous studies in adult models: ANP increased renal vascular resistanc e in the isolated perfused rat kidney (25), and in some reports, but not others (26), ANP administered in vivo decreased renal blood flow in the euvolemic adult rat.…”
Section: Discussionmentioning
confidence: 58%
“…Circulating ANP concentrations are elevated in human fetuses with chronic anemia due to isoimmuni zation (5), as well as in experimental models of fetal hydrops and polyhydramnios (6), and ANP has been implicated in the pathogenesis of these conditions because it promotes vascular permeation of fluid and protein in the ovine fetus (7). The obse rvation that exogenously administered ANP causes increased sodium excretion when administered to otherwise normal fetuses (8) suggests that this hormon e may also enhance the natriuresis in prolonged fetal anemia.…”
Section: Endogenous Anp In Chronic Fetal Anemia 723mentioning
confidence: 99%